Response Surface methodology for the optimized production of polylactide from lactic Acid produced by lactobacillus delbrueckii - Gaurava S.; Pradeep S. (My University, 2025)
Response surface methodology involving central composite design was successfully applied to evaluate the optimized conditions for the polymerization of lactic acid to produce polylactide. Effect of different parameters such as temperature, time and catalyst concentration for polymerization of lactic acid was optimized. Statistical analysis of the results showed that the quadratic terms of these three variables had significant effect. The interaction between the three variables was found to contribute to the response at significant level. A quadratic model was developed through RSM in terms of independent variables to describe experimental yield as the response. Based on contour, 3D-plots and variance analysis, optimum operational conditions for maximizing initial experimental yield were determined. Maximum polylactide production achieved was at time 15 hrs, temperature 165 °C and catalyst concentration 0.06%. Experimental findings were in dose agreement with the model predictions.